Design and Implementation of Internet Protocol - Khalil Murtadha, Muayad (Journal of Engineering and Sustainable Development, 2013)
Determining the geographic location of an Internet Protocol (IP) devices based on its IP addresses is a challenging matter because of wide network topologies and many protocols used to interconnect these devices. On the other hand, the Internet Protocol does not contain any geographic information; they contain routing information, therefore some geolocation techniques should be developed to solve this matter. Today, finding the geographic location of an IP address becomes more important for many applications like local aware applications and restricted content delivery based on IP location. This work presents the design and implementation of IP location determination system which has been developed using the network of Computer center of University of Baghdad. In this system, a network entity called a Location Information Server (LIS) is defined to exist within the access network used to provide location information to IP devices operating within the access network. The designed system provides solutions that meet the requirements for determining the location of Private IP address inside Local Area Network (LAN), also, it describes the geographic location of Public IP address on the internet.